Online teaching challenges: the role of created audiovisual aids in teaching Arabic to non-Arab speakers at schools - Brioua, Nadira; Ahmad H.Osman, Rahmah; Ahmed Mahmoud, Ahmed Ragheb (INT-JECSE, 2022)
Background and Purpose: There are many difficulties which both Arabic teachers and non-Arab speakers encounter in the process of learning Arabic language. Covid- 19 has made online teaching inevitable. The role of created audio-visual aids in teaching Arabic to non-Arab students as well as the challenges faced by students learning through online classes is explored. The criteria for creating audio-visual aids and their effects is also investigated. Methodology:A descriptive analysis method is adopted to describe the challenges and difficulties that foundation and primary students face when learning Arabic via online-based means and to analyse the effects of the created audio-visual aids on students. A questionnaire was distributed to 79 foundation and primary students. Findings:Itwasfound that the usage and application of audio-visual tools in online-based teaching effectively eases students’ interaction with one another, contributed to better academic achievementincreased their vocabulary, enabling them to construct simple short sentences. It has also changed the students’ perception of Arabic and instilled a passion for learning Arabic. Contributions: The study substantiates that the usage of audio-visual aids in online Arabic teaching is a key component to help non-Arab studentsto learn Arabic easily and effectively online.